Adhesion in non-carious cervical lesions: Literature review (Research, Society and Development, 2025)
Objective: To review the scientific literature on current adhesive procedures in non-carious cervical lesions (NCCLs), addressing their compositions, techniques, bond strength of the products, and clinical longevity. Methodology: This is a narrative literature review conducted using the PubMed and Google Scholar databases. Descriptors in Portuguese (DeCS) and English (MeSH) were used, combined with Boolean operators, with inclusion criteria focused on relevant clinical studies about adhesion in NCCLs. Results: The selection of an appropriate adhesive system varies according to lesion characteristics. Universal adhesives, conventional multi-step adhesives, and resin-modified glass ionomer cements demonstrated clinical efficacy. However, the presence of sclerotic dentin, difficulty in cervical isolation, and occlusal forces compromise restoration longevity. Strategies such as selective enamel etching and dentin surface treatment improve adhesive retention. Conclusions: Treatment of NCCLs requires an individualized approach based on scientific evidence, technical knowledge, and careful selection of materials. The development of new biomaterials and long-term clinical studies are essential for advancing this field.